Sonographic Features of Superficial‐Type Nodular Fasciitis in the Musculoskeletal System. (1st August 2015) - Lee, Kyung Jin; Jin, Wook; Kim, Gou Young; Rhee, Sun Jung; Park, So Young; Park, Ji Seon; Ryu, Kyung Nam
Abstract : Objectives: We evaluated the sonographic features of superficial‐type nodular fasciitis in 9 pathologically proven cases. Methods: Review of the radiology and pathology databases yielded 14 cases of histologically proven superficial‐type nodular fasciitis, which was defined as nodular fasciitis located in the subcutaneous fat layer or outer muscle fascia between the subcutaneous fat layer and muscle. Sonograms were available in 9 patients. Two musculoskeletal radiologists retrospectively reviewed all cases in consensus. Imaging features evaluated included the fasciitis location in the body, size, relationship with the fascia, echogenicity, vascularity, and location of the center. Results: There were 4 male and 5 female patients. The mean age was 35 years (range, 8–49 years). The masses ranged in size from 0.8 to 2 cm, with 90% measuring less than 1.8 cm. Five masses developed in the forearm (4 cases) or elbow (1 case). Six masses were located in the subcutaneous fat layer, and 3 masses were in the fascia. Seven masses were in direct contact with the outer muscle fascia, whereas 2 masses were indistinctly in contact with the fascia. These masses showed a hypoechoic background with echogenic foci or peripheral hyperechoic nodules. In all 3 of the masses within the fascia, the findings were similar to those of neurogenic tumors. The vascularity of the masses was variable, but most (7 of 9 cases) showed no substantial vascularity. All masses had centers of less than half the thickness of the subcutaneous fat layer. Conclusions: Superficial‐type nodular fasciitis is often located in the deep subcutaneous fat near the muscle fascia, has a hypoechoic appearance with echogenic foci or peripheral hyperechoic nodules, and quite often does not show internal vascular flow. If a superficial soft tissue mass has the above findings, superficial‐type nodular fasciitis should be included in the differential diagnosis.